Effectiveness of Transit Oriented Development in Reducing Car Use: Case Study of Subiaco, Western Australia - Griffiths, B.; Curtis, Carey (Routledge, 2017)
A transit oriented development (TOD) approach for Perth, Western Australia has been employed as one means of reducing car dependency. Planning for Subiaco Station precinct, one of the first Perth TOD precincts, commenced two decades ago. Drawing on a resident survey, an analysis of the extent that TOD has influenced transport mode choice is provided. The findings reveal that, over time, public transport use has increased and car use decreased, but the latter remains the primary mode of transport. Further reductions in car use could be achieved by addressing “within precinct” factors including improving the quality of pedestrian infrastructure and reducing generous car parking standards; and “beyond precinct” by improving metropolitan wide public transport accessibility in order to better link the precinct to other destinations. In addition to precinct design, addressing attitudes towards car use is necessary in order to change behaviour.